Encapsulated transition metal oxide nanorods for durable air cathodes
Patent Information
- Application Number
- JP2026501483
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-11
- Filing Date
- 2024-07-10
- Publication Date
- 2026-10-16
Smart Images

Figure 2026534428000001 
Figure 2026534428000002 
Figure 2026534428000003
Abstract
Description
[Technical Field]
[0001] This application claims priority to European Patent Application No. 23382707.0, filed on 11 July 2023.
[0002] This disclosure relates to the field of nanomaterials. In particular, the present invention relates to hybrid materials comprising transition metal oxide nanorods, such as manganese oxide nanorods, encapsulated within open-end hollow carbon nanostructures. The present invention also relates to the preparation process of hybrid materials and their use as electrode catalysts in both the fields of energy storage and energy conversion. [Background technology]
[0003] Electrically rechargeable zinc-air batteries are proposed as a promising alternative for future sustainable energy storage thanks to their high theoretical energy density, the use of abundant and environmentally friendly materials, and their safety. However, the economic potential and efficiency of these batteries are not currently satisfactory. Limitations in achieving high reversibility, i.e., long life, are related to both the zinc anode and the dual-function air electrode (cathode). There are ways to significantly improve the reversibility of the zinc anode. However, the lack of approaches to address the limitations of the cathode significantly hinders the practical application and commercialization of current secondary zinc-air batteries.
[0004] Rapid degradation of the cathode material (e.g., loss of the catalyst's active surface area) leads to a rapid decrease in (storage) capacity. Meanwhile, the efficiency and power density of rechargeable zinc-air batteries are severely limited by the slow reaction rates of the oxygen reduction (ORR) and oxygen evolution (OER) reactions occurring at the air electrode. While ORR is thermodynamically favorable, both ORR and OER are kinetically hindered. Therefore, a material is required that is not only durable but also catalytically active for both reactions (a bifunctional material).
[0005] Furthermore, the difficulty for reactants (gas molecules and ions) to approach the catalytic active center further reduces the activity of the electrode catalyst material. The lack of large-scale, low-cost manufacturing methods for highly durable catalysts that enable precise porosity control to ensure efficient mass transport and electron transfer pathways simultaneously is currently hindering the scale-up of zinc-air batteries for applications.
[0006] Materials based on platinum, palladium, or other precious metals and their oxides (e.g., iridium oxide) have been successfully used as electrocatalysts for either ORR or OER. Nevertheless, their limited availability and high cost prompt researchers to explore alternative electrocatalysts. Within this framework, transition metal oxides, particularly manganese and iron oxide, have attracted considerable interest due to their high specific capacity, abundance, low cost, great versatility, and non-toxicity. Unfortunately, the applicability of these transition metal oxides is limited by dissolution during electrochemical processes occurring at the electrode surface. As mentioned above, this electrode degradation is a major technical obstacle in energy storage and conversion applications, as the loss of active material means a loss of activity, and therefore a loss of efficiency in the processes involved.
[0007] With this in mind, efforts have been made to develop nanomaterials based on transition metal oxides to maximize electrocatalytic activity while improving conductivity and maintaining an accessible surface area. In the field of nanomaterial development, it has been shown that there is a close relationship between the structure (morphology) of a material and its properties. This is because certain morphologies expose more of certain crystal planes than other morphologies. Despite these advances, the considerable effort to synthesize these active materials is often still masked by low stability and durability, and they lose much of their initial catalytic capacity when used. One strategy that has been used to reduce the dissolution of metal oxides is to coat the surface of the oxide. However, in these coated materials, the increase in stability usually comes at the expense of their activity, and furthermore, the synthesis of these coated materials is complex.
[0008] Therefore, there remains a need to develop active and stable materials that can be effectively used as electrode catalysts on an industrial scale, for example, in zinc-air batteries. [Overview of the Initiative]
[0009] The inventors have developed novel hybrid materials comprising transition metal oxide nanorods, particularly manganese(IV) oxide, cobalt(III) oxide, nickel(III) oxide, and iron(III) oxide, which are encapsulated within open-end hollow carbon nanostructures. The hybrid oxide materials can optionally be doped with other metals, as specified herein. z M' 2y Mn 1-x O2@CN and rM” 3m / n M 2-m Also known as O3@CN, the formula is where A is a monovalent metal, M, M', and M'' are transition metals as defined herein, and CN represents an open-end carbon nanostructure.
[0010] These materials can be used, more specifically in the context of electrochemical technologies used for energy conversion and storage, as electrode materials in metal-air (e.g., Zn-air) batteries, acting as electrode catalysts in bifunctional air electrodes to enhance durability and reversibility during charging and discharging processes.
[0011] The inventors have found that these transition metal oxide particles in the form of nanorods, particularly manganese(IV) oxide, cobalt(III) oxide, nickel(III) oxide, and iron(III) oxide particles, as well as their doped forms, result in a highly stable structure, not only in terms of a low tendency to aggregate, which allows them to maintain a constant active surface area, but also in terms of low solubility, which allows them to maintain active crystal planes.
[0012] One-dimensional morphology (i.e., nanorods) provides a large contact area with the substrate, which promotes its electrocatalytic capability in the water oxidation process performed, for example, in a zinc-air battery (Figure 16), and better withstands structural changes associated with ion intercalation or deintercalation (meaning increased cyclability) compared with other morphologies. These two properties lead to improved electrochemical parameters with respect to reversibility and the ability to withstand high charge-discharge currents.
[0013] Furthermore, when transition metal oxide nanorods, particularly manganese(IV) oxide, cobalt(III) oxide, nickel(III) oxide, and iron(III) oxide nanorods as well as their doped forms, are confined within open-ended hollow carbon nanostructures acting as nanocontainers, a strong interaction occurs between the nanoparticles and the carbon surface, so that the inherently low electrical conductivity of the metal oxides is improved.
[0014] Without being bound by theory, as a result of nanorod encapsulation in the confined space, Mn 2+ , Co 2+ , Ni 2+ , or Fe 2+ diffusion into the electrolyte is restricted, and upon reaching a positive potential, their recapture by deposition as oxides (e.g., MnO₂ when the transition metal is manganese) is believed to be facilitated. Therefore, since the transition metal oxide nanorods are encapsulated inside the open-ended hollow carbon nanostructures, the loss of active material at the electrode due to dissolution, which is a direct cause of the low stability of metal oxides, is minimized. This is illustrated in the example of the precursor s-Mn₃O₄@CNF, see Figure 12a to Figure 12b. In contrast, an analog material comprising nanoparticles deposited on the outside of the nanofibers (s-Mn₃O₄@CNF) was found to have low stability (Figure 13).
[0015] Unlike the case of coating materials where increased stability usually sacrifices their activity, in the hybrid material of the present invention, dissolution of the material is not inhibited, and Mn 2+ , Co 2+ , Ni 2+ , or Fe2+ Only the diffusion of cations into the electrolyte is reduced. In this invention, as shown in the examples, encapsulation does not inhibit the intrinsic reactivity of the nanoparticles (Figure 14), i.e., the dissolution process continues.
[0016] The material of the present invention is referred to herein as sR t M"' 3-t Also known as O4@CN, R and M''' are transition metals as defined herein, and can be conveniently obtained by electrosynthesis from precursor materials containing spherical nanoparticles composed of transition metal (II,III) oxides, particularly manganese (II,III) oxides, already encapsulated within open-end hollow carbon nanostructures. CN represents the open-end carbon nanostructure.
[0017] Electrochemical (or electrosynthetic) processes have proven to be highly versatile and a viable alternative to hydrothermal processes that require large amounts of solvent, high temperatures, or high pressures. We have found that by controlling electrochemical parameters such as sweep potential, current density, or electrolyte composition, it is possible to obtain desired forms of materials in the form of nanorods (Figure 2).
[0018] Precursor material (sR t M"' 3-t O4@CN) can be synthesized by a very simple and rapid process, as it involves a single step and can typically be carried out in a reaction time of about 1–3 hours. These characteristics facilitate the implementation of the process on an industrial scale. Furthermore, the process is cost-effective because it can use only inexpensive metals such as manganese or iron salts, and the reaction temperature is quite low (typically around 90°C), which allows the use of low-melting-point organic solvents (e.g., xylene) in contrast to other more common solvents in the synthesis of metal oxide nanoparticles such as diphenyl ether, 1-octadecene, or trioctadecene (i.e., 260°C, 317°C, and 365°C, respectively).
[0019] Furthermore, the process for preparing the materials of the present invention is highly versatile because it allows for the incorporation of other transition metals, typically in small amounts, into the crystal structure of first transition metal oxides, particularly manganese oxide, cobalt oxide, nickel oxide, and iron oxide, substituting Mn or M atoms with other cations to produce doped materials. As shown in the following examples, by simply replacing some of the starting manganese salts used to prepare precursor-encapsulated spherical nanoparticles with other transition metal salts, such as cobalt, nickel, or iron salts, it is possible to obtain doped materials (Figures 3-10) with different applicability depending on their reactivity (Figure 11). The formation of doped nanorods inside nanofibers after electrosynthesis (Figures 18-20) results in materials with high stability and activity (Figure 17), making it possible to generate a family of one-dimensional polymetallic nanostructures inside carbon nanofibers applicable in various fields.
[0020] Therefore, a first aspect of the present invention relates to a material comprising a plurality of nanorods encapsulated within an open-end hollow carbon nanostructure, wherein the plurality of nanorods are a) Transition metal oxides of formula (A) A z M' 2y Mn 1-x O2 (A) or, b) Transition metal oxides of formula (B) M" 3m / n M 2-m O3 (B) consists of, During the ceremony, In equation (A), A is a monovalent metal, M' is a transition metal other than Mn in a divalent oxidation state, x is equal to (z / 4+y) such that 0≦y<1 and 0≦z<4, manganese can be in either the oxidation state of (IV) or a mixture of (IV) and (III), the latter of which shows an oxygen vacancy. In equation (B), M is a transition metal in a trivalent oxidation state selected from iron, cobalt, and nickel, M'' is a transition metal that is equal to or different from M in oxidation state n, where n is a value between 2 and 6, and 0 ≤ m < 2. The transition metal oxide of formula (A) or formula (B) is present in an amount of 20-60% by weight relative to the total weight of the material. The volume of the nanorods encapsulated within the hollow carbon nanostructure is less than 50% of the total cavity volume of the hollow carbon nanostructure. In particular, the hollow carbon nanostructure is tubular, and its inner diameter is at least twice the average thickness of the nanorods.
[0021] A second aspect of the present invention relates to an electrochemical process for preparing a material comprising a plurality of nanorods composed of a transition metal oxide as defined herein, wherein the process comprises: i) A step of providing a modifying electrode by coating a conductive surface with a precursor material comprising a plurality of spherical nanoparticles composed of transition metal (II,III) oxides of formula (C), R t M"' 3-t O4 (C) The spherical nanoparticles are encapsulated within open-end hollow carbon nanostructures, in the formula, M''' is a transition metal selected from the group consisting of manganese, iron, cobalt, and nickel in divalent and trivalent oxidation states. R is a transition metal other than M''' in the divalent oxidation state. t is a value between 0 and 1, and is greater than or equal to 0. The transition metal oxide in formula (C) is present in an amount of 20-60% of the total weight of the material. The volume of spherical nanoparticles encapsulated within the hollow carbon nanostructure is 50% or less of the total cavity volume of the hollow carbon nanostructure, and in particular, the hollow carbon nanostructure is tubular, and its inner diameter is at least twice the average thickness of the nanorods, step, ii) A step of electrosynthesis of an aqueous solution containing an electrolyte selected from the group consisting of an alkali or alkaline earth metal halide salt or an alkali or alkaline earth metal hydroxide, using a counter electrode, a reference electrode, and the modifying electrode obtained in step i), iia) Apply a constant current cycle of 5000 times or less at a current density of 0.5A or more per g of precursor material, in the range of -0.2 to 0.8V, iib) A step which is performed by applying 5000 or fewer dynamic cycles in the range of 1 to 1.7 V at a scanning speed of 40 mV / s or more.
[0022] In the above process, when M''' in the precursor material of formula (C) is manganese, a material is obtained that contains multiple nanorods encapsulated within an open-end hollow carbon nanostructure, where the multiple nanorods are composed of a transition metal oxide of formula (A). Furthermore, when M''' in the precursor material of formula (C) is a transition metal selected from the group consisting of iron, cobalt, and nickel, a material is obtained that contains multiple nanorods encapsulated within an open-end hollow carbon nanostructure, where the multiple nanorods are composed of a transition metal oxide of formula (B).
[0023] A third aspect of the present invention relates to a precursor material comprising a plurality of spherical nanoparticles composed of a transition metal (II,III) oxide of formula (C), R t M"' 3-t O4 (C) The spherical nanoparticles are encapsulated within open-end hollow carbon nanostructures, in the formula, M''' is a transition metal selected from the group consisting of manganese, iron, cobalt, and nickel in divalent and trivalent oxidation states. R is a transition metal other than M''' in the divalent oxidation state. t is a value between 0 and 1, and is greater than or equal to 0. The transition metal oxide in formula (C) is present in an amount of 20-60% of the total weight of the material. The volume of spherical nanoparticles encapsulated within the hollow carbon nanostructure is 50% or less of the total cavity volume of the hollow carbon nanostructure. In particular, the hollow carbon nanostructure is tubular, and its inner diameter is at least twice the average diameter of the spherical nanoparticles.
[0024] A fourth aspect of the present invention relates to a process for preparing a precursor material as defined herein, the process being: a) Providing a mixture of a transition metal(II) salt and optionally a second salt of a transition metal other than a first transition metal having a divalent oxidation state, in the presence of a surfactant in a suitable solvent, wherein the metal of the first transition metal(II) salt is selected from manganese, iron, and cobalt, and the metal of the second salt is other than the metal of the first salt; b) Adding the mixture from step a) to a suspension of open-end hollow carbon nanostructures in a suitable solvent, c) The step of heating the suspension to a temperature of 80-110°C, d) Add water to the suspension from step c) and heat to a temperature of 80-110°C to obtain a precursor material of formula (C), and the process includes the steps of: When step a) is carried out in the absence of another salt of the transition metal, a material of formula (C) is obtained, where t is 0. When step a) is carried out in the presence of a second salt of the transition metal, a precursor material of formula (C) is obtained, where t is different from 0 and R is a transition metal other than M''' in a divalent oxidation state.
[0025] A fifth aspect of the present invention relates to the use of a material comprising a plurality of nanorods as defined above as an electrode catalyst. [Brief explanation of the drawing]
[0026] [Figure 1] Bright-field transmission electron microscope (TEM) image (a), dark-field scanning mode (STEM) image (b), and energy-dispersive X-ray (EDX) spectroscopy elemental mapping images of oxygen (c), carbon (d), and manganese (e) for s-Mn3O4@CNF are shown. Scale bars: (a) 100 nm and (b~e) 20 nm. [Figure 2]Bright-field TEM image (a), dark-field STEM image (b), EDX elemental mapping images of carbon (c), oxygen (d), and manganese (e) within carbon nanofibers (r-MnO2@CNF), as well as EDX spectrum (f) (C: count, E: energy; presence of Cu is due to the use of a Cu TEM grid). Scale bars in all images are 100 nm. Inset in (a): Example of a rod with crystal planes (interplanar spacing (d=0.34 nm)) related to the MnO2 crystal structure (pyrolsite type). [Figure 3] Raman spectra are shown for (a) undoped manganese oxide nanoparticles (s-Mn3O4@CNF) in carbon nanofibers, (b) cobalt-doped manganese oxide nanoparticles (s-Co / Mn3O4@CNF) in carbon nanofibers, (c) nickel-doped manganese oxide nanoparticles (s-Ni / Mn3O4@CNF) in carbon nanofibers, (d) iron-doped manganese oxide nanoparticles (s-Fe / Mn3O4@CNF) in carbon nanofibers, (e) undoped cobalt oxide nanoparticles (s-Co3O4@CNF) in carbon nanofibers, and (f) undoped iron oxide nanoparticles (s-Fe3O4@CNF) in carbon nanofibers. C: count, RS: Raman shift. [Figure 4] X-ray powder diffractograms are shown for (a) undoped manganese oxide nanoparticles (s-Mn3O4@CNF) in carbon nanofibers, (b) cobalt-doped manganese oxide nanoparticles (s-Co / Mn3O4@CNF) in carbon nanofibers, (c) nickel-doped manganese oxide nanoparticles (s-Ni / Mn3O4@CNF) in carbon nanofibers, (d) iron-doped manganese oxide nanoparticles (s-Fe / Mn3O4@CNF) in carbon nanofibers, (e) undoped cobalt oxide nanoparticles (s-Co3O4@CNF) in carbon nanofibers, and (f) undoped iron oxide nanoparticles (s-Fe3O4@CNF) in carbon nanofibers. I: Intensity. [Figure 5]The following are thermogravimetric analysis (TGA) measurements under air for (a) undoped manganese oxide nanoparticles (s-Mn3O4@CNF) in carbon nanofibers, (b) cobalt-doped manganese oxide nanoparticles (s-Co / Mn3O4@CNF) in carbon nanofibers, (c) nickel-doped manganese oxide nanoparticles (s-Ni / Mn3O4@CNF) in carbon nanofibers, (d) iron-doped manganese oxide nanoparticles (s-Fe / Mn3O4@CNF) in carbon nanofibers, (e) undoped cobalt oxide nanoparticles (s-Co3O4@CNF) in carbon nanofibers, and (f) undoped iron oxide nanoparticles (s-Fe3O4@CNF) in carbon nanofibers. w: weight, T: temperature, L: percentage of metal oxide remaining after annealing at 1000°C. [Figure 6] Histograms of particle size distributions are shown for (a) undoped manganese oxide nanoparticles (s-Mn3O4@CNF) in carbon nanofibers, (b) cobalt-doped manganese oxide nanoparticles (s-Co / Mn3O4@CNF) in carbon nanofibers, (c) nickel-doped manganese oxide nanoparticles (s-Ni / Mn3O4@CNF) in carbon nanofibers, (d) iron-doped manganese oxide nanoparticles (s-Fe / Mn3O4@CNF) in carbon nanofibers, (e) undoped cobalt oxide nanoparticles (s-Co3O4@CNF) in carbon nanofibers, and (f) undoped iron oxide nanoparticles (s-Fe3O4@CNF) in carbon nanofibers. C: count, D: nanoparticle diameter. [Figure 7] Bright-field TEM images (a) of cobalt-doped manganese oxide nanoparticles (s-Co / Mn3O4@CNF) within carbon nanofibers, dark-field EDX-STEM elemental mapping images of manganese (b), carbon (c), oxygen (d), and cobalt (e), and EDX spectra (f) (C: count, E: energy; presence of Cu is due to the use of a Cu TEM grid). All image scale bars are 100 nm. [Figure 8]Bright-field TEM images (a) of nickel-doped manganese oxide nanoparticles (s-Ni / Mn3O4@CNF) within carbon nanofibers, dark-field EDX-STEM elemental mapping images of manganese (b), carbon (c), oxygen (d), and nickel (e), and EDX spectral analysis (f) (C: count, E: energy; presence of Cu is due to the use of a Cu TEM grid) are shown. All image scale bars are 100 nm. [Figure 9] Bright-field TEM images (a) of iron-doped manganese oxide nanoparticles (s-Fe / Mn3O4@CNF) within carbon nanofibers, dark-field EDX-STEM elemental mapping images of manganese (b), carbon (c), oxygen (d), and iron (e), and EDX spectral analysis (f) (C: count, E: energy; presence of Cu is due to the use of a Cu TEM grid) are shown. All image scale bars are 50 nm. [Figure 10] Cyclic voltammetry of manganese oxide nanoparticles in carbon nanofibers doped with (a) undoped (s-Mn3O4@CNF), (b) cobalt (s-Co / Mn3O4@CNF), (c) nickel (s-Ni / Mn3O4@CNF), and (d) iron (s-Fe / Mn3O4@CNF) is shown in a nitrogen-saturated 1M KOH solution at a scanning speed of 50 mV / s. C: current density, P: potential. [Figure 11] Linear scanning voltammetry is shown for the oxygen evolution reaction (OER, 1~1.8V) and oxygen reduction reaction (ORR, 1V~0.3V) of manganese oxide nanoparticles in undoped (s-Mn3O4@CNF), cobalt-doped (s-Co / Mn3O4@CNF), nickel-doped (s-Ni / Mn3O4@CNF), and iron-doped (s-Fe / Mn3O4@CNF) carbon nanofibers in a 1M O2-saturated KOH solution at a scanning speed of 10mV / s. C: current density, P: potential (RHE: reversible hydrogen electrode). [Figure 12]Bright-field TEM images (a) before and (b) after treatment of unwashed carbon nanofibers (s-Mn3O4@CNF) containing manganese oxide nanoparticles on the outer casing of a nanocontainer, in a nitrogen-saturated 2M KCl solution for 500 cycles (between -0.2 and 0.8V at a scanning speed of 50mV / s). The scale bar is 100nm. [Figure 13] This shows the cyclic voltammetry (n = number of cycles) of unwashed carbon nanofibers (s-Mn3O4@CNF) containing manganese oxide nanoparticles on a nanocontainer in a nitrogen-saturated 2M KCl solution. C: current density, P: potential. [Figure 14] The images show bright-field (a) and dark-field (b) TEM images of manganese oxide nanoparticles in carbon nanofibers (s-Mn3O4@CNF) after several charge-discharge cycles (1500) at 1 A / g in a nitrogen-saturated 2M KCl solution, dark-field EDX-STEM elemental mapping images of carbon (c), oxygen (d), and manganese (e), and EDX spectral (f) analysis (C: count, E: energy; presence of Cu is due to the use of a Cu TEM grid). All image scale bars are 50 nm. [Figure 15] (a) Constant current charging and discharging cycles of manganese oxide nanoparticles in carbon nanofibers at 1 A / g, consisting of 2500 cycles in a nitrogen-saturated 2 M KCl solution, before (s-Mn3O4@CNF, solid dotted line) and after (r-MnO2@CNF, dashed line) electrosynthesis. The solid black line represents carbon nanofibers without manganese oxide nanoparticles. (b) Change in capacity retention (%) as a percentage of the number of cycles. The large (more than 4-fold) improvement in capacity retention is related to the formation of nanorods within the carbon nanofibers. P: potential, T: time, CR: capacity retention, C: number of cycles [Figure 16] (a) Linear scanning voltammetry and (b) Tafel plots of manganese oxide nanoparticles on carbon nanofibers in oxygen-saturated 1M KOH solution before (s-Mn3O4@CNF, solid line) and after (r-MnO2@CNF, dashed line) electrosynthesis (2500 cycles in 2M KCl). C: current density, P: potential. [Figure 17]Linear scanning voltammetry of manganese oxide nanoparticles on (a) cobalt, (b) nickel, and (c) iron-doped carbon nanofibers in oxygen-saturated 1M KOH solution before (solid line) and after (dashed line) electrosynthesis (2500 cycles in 2M KCl or 1M KOH). C: current density, P: potential. [Figure 18] Bright-field TEM images (a), dark-field EDX-STEM elemental mapping images of manganese (b), carbon (c), oxygen (d), and cobalt (e) of cobalt-doped manganese oxide nanorods within carbon nanofibers (r-KCo / MnO2@CNF), and EDX spectral (f) (C: count, E: energy; presence of Cu is due to the use of a Cu TEM grid) analysis are shown. Inset in (a): Example of a rod with crystal planes (interplanar spacing (d=0.49 nm) related to the MnO2 crystal structure (hollandite type inset) having the formula AzM'2yMn1-xO2. Scale bars in all images are 50 nm. [Figure 19] Bright-field TEM images (a), dark-field EDX-STEM elemental mapping images of manganese (b), carbon (c), oxygen (d), and nickel (e), and EDX spectral analysis (f) (C: count, E: energy; presence of Cu is due to the use of a Cu TEM grid) of nickel-doped manganese oxide nanorods within carbon nanofibers (r-KNi / MnO2@CNF) are shown. Inset of (a): Example of a rod with crystal planes (interplanar spacing d=0.24 nm) associated with a MnO2 crystal structure (pyrolsite type, inset) having the formula M'2yMn1-xO2. The scale bar in all images is 50 nm. [Figure 20]Bright-field TEM images (a), dark-field EDX-STEM elemental mapping images of manganese (b), carbon (c), oxygen (d), and iron (e) of iron-doped manganese oxide nanorods within carbon nanofibers (r-KFe / MnO2@CNF), and EDX spectral analysis (f) (C: count, E: energy; presence of Cu is due to the use of a Cu TEM grid) are shown. Inset in (a): Example of interplanar spacing distance (d=0.49 nm) related to a MnO2 crystal structure with potassium ions intercalated with the formula AzM'2yMn1-xO2 (hollandite type inset). Scale bars in all images are 50 nm. [Figure 21] This shows the variation in the amount of cobalt-doped Mn3O4 nanoparticles in CNF (s-Co / Mn3O4@CNF) when 5%, 10%, 15%, and 20% mmol of manganese(II) acetate is replaced with cobalt(II) acetate. [Figure 22] The images show bright-field (a) and dark-field (b) TEM images of iron oxide nanorods within carbon nanofibers (r-Fe2O3@CNF), dark-field EDX-STEM elemental mapping images of carbon (c), oxygen (d), and iron (e), and EDX spectral (f) analysis (C: count, E: energy; presence of Cu is due to the use of a Cu TEM grid). All image scale bars are 50 nm. [Modes for carrying out the invention]
[0027] All terms used herein are to be understood in the ordinary sense known in the art unless otherwise specified. Other, more specific definitions of any particular terms used herein are set forth below and are intended to apply uniformly throughout the specification and claims unless a more explicit definition is provided.
[0028] As used herein, the terms “about” or “approximately” refer to values within a range of ±10% of a given value. For example, the expression “about 10” or “approximately 10” includes ±10% of 10, i.e., from 9 to 11.
[0029] For the purposes of this invention, any given range includes both the lower and upper endpoints of the range. Given ranges such as weight, temperature, and time should be considered approximate unless otherwise specified.
[0030] As used herein, the term “material” refers to a hybrid material which is the result of a combination of at least two different materials, namely, nanoparticles of transition metal oxides of formula (A), (B), or (C), and open-end hollow carbon nanostructures that encapsulate them.
[0031] The term "precursor material" refers to spherical nanoparticles (sR) composed of transition metal (II,III) oxides, particularly manganese (II,III) oxide, iron (II,III) oxide, or cobalt (II,III) oxide, encapsulated within open-end hollow carbon nanostructures. t M"' 3-t This refers to O4@CN). The abbreviation CN used herein refers to an open-end hollow carbon structure.
[0032] As used herein, the term “nanoparticles” may generally refer to both nanorods and nanospheres as defined herein, unless otherwise specified.
[0033] As used herein, the term “multiple” refers to a collection of nanoparticles, i.e., an aggregate of two or more nanoparticles.
[0034] The terms "encapsulated" or "confined" are used interchangeably and mean that the nanoparticles are located inside the open-end hollow carbon nanostructure. Therefore, the nanoparticles are not located on the outer surface of the hollow carbon nanostructure.
[0035] The term "room temperature" refers to the temperature of an environment that is not heated or cooled, and generally ranges from 20 to 25°C.
[0036] The expression "can be obtained by..." is used herein to define the materials or precursor materials of the present invention by their preparation processes and refers to the products that can be obtained through the preparation processes disclosed herein. For the purposes of the present invention, the expressions "can be obtained," "obtained," and similar equivalent expressions are used interchangeably, and in either case, the expression "can be obtained" encompasses the expression "obtained."
[0037] As described above, a first aspect of the present invention relates to a material comprising a plurality of nanorods encapsulated within an open-end hollow carbon nanostructure, wherein the plurality of nanorods are a) Transition metal oxides of formula (A) A z M' 2y Mn 1-x O2 (A) or, b) Transition metal oxides of formula (B) M" 3m / n M 2-m O3 (B) During the ceremony, In equation (A), A is a monovalent metal, M' is a transition metal other than Mn in a divalent oxidation state, x is equal to (z / 4+y) such that 0≦y<1 and 0≦z<4, manganese can be in either the oxidation state of (IV) or a mixture of (IV) and (III), the latter of which shows an oxygen vacancy. In equation (B), M is a transition metal in a trivalent oxidation state selected from iron, cobalt, and nickel, M'' is a transition metal that is equal to or different from M in oxidation state n, where n is a value between 2 and 6, and 0 ≤ m < 2. The transition metal oxide of formula (A) or formula (B) is present in an amount of 20-60% by weight relative to the total weight of the material. The volume of the nanorods encapsulated within the hollow carbon nanostructure is less than 50% of the total cavity volume of the hollow carbon nanostructure. In particular, the hollow carbon nanostructure is tubular, and its inner diameter is at least twice the average thickness of the nanorods.
[0038] In one embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, the present invention relates to a material comprising a plurality of nanorods encapsulated within an open-end hollow carbon nanostructure, wherein the plurality of nanorods are of formula A z M' 2y Mn 1-x It is composed of transition metal (IV) oxides of O2(A).
[0039] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, the present invention relates to a material comprising a plurality of nanorods encapsulated within an open-end hollow carbon nanostructure, wherein the plurality of nanorods are of formula M” 3m / n M 2-m It is composed of a transition metal (III) oxide of O3(B). In a more specific embodiment, in the transition metal (III) oxide of formula (B), M is iron. In another more specific embodiment, in the transition metal (III) oxide of formula (B), M is cobalt. In yet another more specific embodiment, in the transition metal (III) oxide of formula (B), M is nickel.
[0040] According to another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, the transition metal oxide is present in the material at a weight of 20-60%, more specifically 25-55%, and even more specifically 30-40%, relative to the total weight of the material. The amount of the transition metal oxide of formula (A) or formula (B) can be determined by thermogravimetric analysis (TGA).
[0041] The transition metal oxides of formulas (A), (B), or (C) may be doped or undoped. For the purposes of this invention, the term “undoped” means that the transition metal oxide does not contain other metals as dopants. As used herein, the term “doped” refers to a metal oxide that contains impurities (dopants) from different metals and ultimately exhibits modified properties.
[0042] Non-limiting examples of transition metals that can be used in the present invention include manganese, iron, cobalt, nickel, copper, chromium, molybdenum, titanium, vanadium, and zinc.
[0043] Non-limiting examples of alkali metals that can be used in the present invention include sodium, potassium, and cesium.
[0044] According to one embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, the transition metal oxide of formula (A) is undoped, i.e., y and z are 0. In such a case, the transition metal oxide of formula (A) has the formula MnO2.
[0045] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the transition metal oxide is doped, i.e., in the transition metal (IV) oxide of formula (A), at least one of y or z is non-zero, and therefore x is non-zero. More specifically, A is selected from the group consisting of sodium, potassium, and cesium, and M' is selected from the group consisting of manganese, iron, cobalt, nickel, copper, chromium, molybdenum, titanium, vanadium, and zinc. Even more specifically, A is potassium, and M' is selected from the group consisting of iron, cobalt, and nickel. In yet another specific embodiment, y is 0 and z is non-zero. In yet another more specific embodiment, y is non-zero and z is 0. In yet another more specific embodiment, y and z are non-zero independently of 0.
[0046] When z is 0, a pyrolsite-type structure is obtained (see, for example, Figures 1 and 19), and when z is not 0, a hollandite-type structure is obtained (see, for example, Figures 18 and 20).
[0047] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the transition metal oxide is doped, that is, in the transition metal (IV) oxide of formula (A), x is a value greater than 0 and less than 1. In a more specific embodiment, x is 0.01 to 0.4, and even more specifically, x is 0.05 to 0.09. Even more specifically, x is about 0.01, about 0.02, about 0.03, about 0.05, about 0.07, about 0.09, about 0.1, about 0.15, about 0.20, about 0.25, about 0.3, about 0.35, or about 0.4.
[0048] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the present invention relates to a material comprising a plurality of nanorods encapsulated within an open-ended hollow carbon nanostructure, wherein the plurality of nanorods is composed of a mixture of one or more transition metal oxides of formula (A). More specifically, the plurality of nanorods is the metal oxide of formula (A1) M' 2y Mn 1-x’ O2 (A1), and the metal oxide of formula (A2) A z’ M' 2y Mn 1-x” O2 (A2) wherein M' is a transition metal other than Mn in the divalent oxidation state, x' is equal to y, x"=(z' / 4+y), 0≦y<1 and 0<z'<4, A is a monovalent metal, manganese can assume either the oxidation state of (IV) or a mixture of (IV) and (III), and the latter case exhibits oxygen vacancies. The metal oxide of formula (A1) corresponds to the metal oxide of formula (A) when z is 0, and the metal oxide of formula (A2) corresponds to the metal oxide of formula (A) when z is different from 0.
[0049] In more specific embodiments, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the weight ratio of the metal oxide of equation (A1) to the metal oxide of equation (A2) when y=0 is 100:0 to 50:50, more specifically 80:20 to 60:40.
[0050] In another, more specific embodiment, when y=0, the weight ratio of the metal oxide of formula (A1) to the metal oxide of formula (A2) is approximately 100:0, approximately 90:10, approximately 85:15, approximately 80:20, approximately 75:25, approximately 70:30, approximately 65:35, approximately 60:40, approximately 55:45, or approximately 50:50.
[0051] In more specific embodiments, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the weight ratio of the metal oxide of formula (A1) to the metal oxide of formula (A2) when y is different from 0 is 10:90 to 50:50, more specifically 20:80 to 40:60.
[0052] In another, more specific embodiment, the weight ratios of the metal oxide of formula (A1) to the metal oxide of formula (A2) when y is different from 0 are approximately 10:90, approximately 15:85, approximately 20:80, approximately 25:75, approximately 30:70, approximately 33:67, approximately 35:65, approximately 40:60, approximately 45:55, and approximately 50:50.
[0053] According to one embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the transition metal(III) oxide of formula (B) is undoped, i.e., m is 0.
[0054] In another embodiment, in combination with one or more features of the various embodiments described above or below, optionally throughout the entire description, the transition metal(III) oxide is doped, i.e., in the transition metal(III) oxide of formula (B), m is a value greater than 0 and less than 2, and M'' is the same as or other transition metal as M having oxidation states 2 to 6. More specifically, M'' is a transition metal selected from the group consisting of iron, cobalt, nickel, manganese, chromium, molybdenum, titanium, vanadium, and mixtures thereof, and more specifically, chromium and molybdenum.
[0055] In a more specific embodiment, m is 0.01 to 0.4, and more specifically, m is 0.05 to 0.09. More specifically, m is about 0.01, about 0.02, about 0.03, about 0.05, about 0.07, about 0.09, about 0.1, about 0.15, about 0.20, about 0.25, about 0.3, about 0.35, or about 0.4.
[0056] In another embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, in a transition metal oxide of formula (B), M'' is a transition metal other than M.
[0057] In another embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, in the transition metal oxide of formula (B), M'' is the same transition metal as M.
[0058] In another embodiment, optionally combined with one or more features of the various embodiments described above or below, in the transition metal oxide of formula (B), n is a value from 2 to 6, more specifically, n is selected from the group of metals having oxidation states 2, 3, 4, 5, and 6.
[0059] The transition metal(IV) oxide of formula (A) or the transition metal(III) oxide of formula (B) are in the form of nanorods. For the purposes of this invention, the terms “nanorod” and “nanowire” are used interchangeably and refer to nanoparticles having a narrow dimension (i.e., thickness) and a long dimension (i.e., length), where the ratio of the long dimension to the narrow dimension (i.e., aspect ratio) is 2 or greater. The narrow dimension or diameter corresponds to the shortest dimension or cross-sectional thickness of the nanorod and is essentially constant along the length of a given nanorod. The long dimension or length corresponds to the longest dimension of the nanorod, which is approximately perpendicular to the diameter of the nanorod. The diameter and length of the nanorod can be measured by methods well known in the art, such as transmission electron microscopy (TEM). Typically, average thickness and average length values are given. The term “average thickness” refers to the average value obtained from at least 20 different diameter measurements. The term “average length” refers to the average value obtained from at least 20 different length measurements.
[0060] According to one embodiment, in any combination with one or more features of the various embodiments described above or below throughout the entire description, the nanorod has an average thickness of at least 5 nm, more specifically 5 to 20 nm, even more specifically 8 to 16 nm, and even more specifically about 5 nm, about 5.5 nm, about 6 nm, about 6.5 nm, about 7 nm, about 7.5 nm, about 8 nm, about 8.5 nm, about 9 nm, about 9.5 nm, about 10 nm, about 10.5 nm, about 11 nm, about 11.5 nm, about 12 nm, about 12.5 nm, about 13 nm, about 13.5 nm, about 14 nm, about 15 nm, about 16 nm, about 17 nm, about 18 nm, about 19 nm, or about 20 nm.
[0061] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the nanorod has an average length of at least 16 nm, more specifically 16 to 180 nm, and more specifically 50 to 150 nm.
[0062] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the nanorod exhibits an aspect ratio of 2 to 15, more specifically 3 to 10.
[0063] In another embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, the nanorod is 280 nm 2 More specifically, 14500nm 2 It has the following surface area.
[0064] The materials of the present invention further include open-end hollow carbon nanostructures. As used herein, the term “hollow carbon nanostructure” refers to a three-dimensional structure having an open interior, such as a tubular, spherical, or polyhedral structure, where one or more ends, particularly two ends, of the hollow portion are open. This allows an electrolyte to flow easily through the interior of the carbon nanostructure.
[0065] According to one embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, the hollow carbon nanostructure is a hollow tubular carbon nanostructure. As used herein, the term “hollow tubular carbon nanostructure” refers to a carbon material in the form of a tube having a continuous closed wall along its length, the tube being open at two opposing ends. In particular, the hollow tubular carbon nanostructures referred to herein have a circular cross-section.
[0066] In a particular embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the amount of open-end hollow carbon nanostructures in the material is 40–80% by weight, more specifically 45–75%, and even more specifically 60–70% of the total weight of the material.
[0067] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the open-end hollow carbon nanostructure is selected from carbon nanotubes, graphitized carbon nanotubes, heteroatom-doped carbon nanotubes, carbon nanofibers, graphitized carbon nanofibers, and heteroatom-doped carbon nanofibers, and more specifically, the hollow carbon nanostructure is a hollow tubular carbon nanostructure selected from carbon nanotubes and carbon nanofibers, and even more specifically, a carbon nanofiber.
[0068] For the purposes of this invention, the term "heteroatom doping" refers to the intercalation and / or incorporation of heteroatoms into carbon nanostructures. Examples of heteroatoms include, but are not limited to, nitrogen, sulfur, phosphorus, boron, silicon, and aluminum.
[0069] The term “open-end hollow carbon nanotube,” also referred to herein simply as CNT, refers to a hollow material consisting of a cylindrically wound graphene sheet, where the graphene layer forms two or more concentric cylinders along the tube axis.
[0070] The term “hollow carbon nanofiber,” also simply referred to herein as CNF, consists of graphene sheets tilted at a specific angle with respect to their principal axis, thus forming stacks of nanocones. CNFs differ from carbon nanotubes in that this angle is equal to 0 in CNTs.
[0071] CNTs and CNFs can be prepared by methods well known in the art, such as chemical vapor deposition (CVD) from hydrocarbons. They are also commercially available. Graphitized carbon nanofibers can be prepared, for example, from carbon nanofibers by heating under appropriate conditions, such as heating at about 1000°C in an inert (argon) atmosphere.
[0072] The diameter and length of CNTs and CNFs can be measured by methods well known in the art, such as transmission electron microscopy (TEM). Typically, average inner and outer diameters and average length values are given. The average inner diameter is smaller than the average outer diameter. The term "average diameter" refers to the average value obtained from at least three different diameter measurements. The term "average length" refers to the average value obtained from at least three different length measurements.
[0073] In one embodiment, the hollow tubular carbon nanostructure has an average inner diameter of 20–180 nm, 30–180 nm, or 40–100 nm, more specifically 60–80 nm, and even more specifically about 70 ± 20 nm, in combination with one or more features of the various embodiments described above or below throughout the entire description.
[0074] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the hollow tubular carbon nanostructure has an average outer diameter of 40–200 nm or 60–140 nm, more specifically 80–130 nm, and even more specifically about 110 nm ± 30 nm.
[0075] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the hollow tubular carbon nanostructure has a length of 10 μm or less, more specifically 1 to 10 μm, and even more specifically 1 to 2 μm.
[0076] In one embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the hollow tubular carbon nanostructure has i) an average inner diameter of 20-180 nm or 30-180 nm or 40-100 nm, more specifically 60-80 nm, and more specifically about 70 ± 20 nm; ii) an average outer diameter of 40-200 nm, more specifically 80-130 nm or 60-140 nm, and more specifically about 110 nm ± 30 nm, provided that the average inner diameter is smaller than the average outer diameter; and iii) a length of 10 μm or less, more specifically 1-10 μm, and more specifically 1-2 μm.
[0077] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, the present invention relates to a material comprising a plurality of nanorods composed of transition metal oxides encapsulated within open-end hollow carbon nanostructures as defined herein.
[0078] As described above, in the material of the present invention, multiple nanorods composed of transition metal oxides are encapsulated within open-end hollow carbon nanostructures. Typically, the average thickness of the nanorods is much smaller than the internal space of the hollow carbon nanostructure; that is, the nanorods do not occupy the entire cavity of the internal carbon nanostructure. In particular, when the hollow carbon nanostructure is a hollow tubular carbon nanostructure, the average thickness of the nanorods is much smaller than the inner diameter.
[0079] In the material of the present invention, the internal cavities of the hollow carbon nanostructure are partially filled only with multiple nanorods composed of transition metal (IV) oxides. In particular, the volume of the nanorods encapsulated within the hollow carbon nanostructure is 50% or less of the total cavity volume of the hollow carbon nanostructure.
[0080] In one embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the volume of the nanorods encapsulated within the hollow carbon nanostructure is 45% or less, 40% or less, 35% or less, 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, 5% or less, 4% or less, 3% or less, 2% or less, or 1% or less, relative to the total cavity volume of the hollow carbon nanostructure.
[0081] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, the volume of the nanorods encapsulated within the hollow carbon nanostructure is 5% or less of the total cavity volume of the hollow carbon nanostructure for rods in the range of 8 to 14 nm in diameter confined within a hollow tubular carbon nanostructure with an inner diameter of approximately 70 nm.
[0082] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, the multiple nanorods do not block the internal space of the hollow tubular carbon nanostructure.
[0083] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, the average inner diameter of the hollow carbon nanostructure is at least twice the average thickness of the nanorod.
[0084] As a result of the fact that the packing volume of 50% or less and / or the average inner diameter of the hollow carbon nanostructure is at least twice the average thickness of the nanorod, all rods are accessible to the electrolyte, which translates to a larger surface area, promoting the flow / diffusion of reactants / products.
[0085] In one embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the inner diameter of the hollow carbon nanostructure is at least twice the average thickness of the nanorod, more specifically 2 to 20 times, even more specifically 3 to 10 times, and even more specifically about 2 times, about 3 times, about 4 times, about 5 times, about 6 times, about 7 times, about 8 times, about 9 times, about 10 times, about 11 times, about 12 times, about 13 times, about 14 times, about 15 times, about 16 times, about 17 times, about 18 times, about 19 times, and about 20 times.
[0086] In another embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, a plurality of nanorods composed of transition metal oxides are arranged on the inner surface of a hollow carbon nanostructure. Thus, in this embodiment, the central part of the cavity of the hollow carbon nanostructure is empty.
[0087] A further advantage of arranging nanorods on the inner surface of carbon nanostructures is that close contact is formed between the metal oxide nanoparticles and the support (carbon nanostructure), and the high conductivity of carbon improves electrical transfer. This close contact is a result of the nanorod preparation process, i.e., the electrochemically induced in-situ transformation process of the precursor. Thus, in one embodiment, and optionally combined with one or more features of the various embodiments described above or below, the metal oxide nanoparticles and hollow carbon nanostructures are in close contact throughout the entire description.
[0088] As described above, the materials of the present invention are prepared by an electrochemical process that has advantages over conventional hydrothermal processes. Accordingly, according to a second aspect, the present invention relates to an electrochemical process for preparing the materials defined herein, wherein the process is i) Formula R as defined herein t M"' 3-tThe step of providing a modifying electrode by coating a conductive surface with a precursor material comprising multiple spherical nanoparticles encapsulated within open-end hollow carbon nanostructures, which are composed of O4(C) transition metal (II,III) oxides. ii) Using the counter electrode, reference electrode, and the modifying electrode obtained in step i), electrosynthesis of an aqueous solution containing an electrolyte selected from the group consisting of alkali or alkaline earth metal halide salts or alkali or alkaline earth metal hydroxides is performed. iia) A step of applying a constant current cycle of 5000 or less cycles in the range of -0.2 to 0.8 V with a current density of 0.5 A or more per g of precursor material, or iib) The step of applying 5000 or fewer dynamic cycles in the range of 1 to 1.7V at a scanning speed of 40mV / s or more, In the precursor material of formula (C), when M''' is manganese, a material is obtained that contains multiple nanorods encapsulated within an open-end hollow carbon nanostructure, the multiple nanorods being composed of a transition metal oxide of formula (A). In the precursor material of formula (C), when M''' is a transition metal selected from the group consisting of iron, cobalt, and nickel, a material is obtained that contains multiple nanorods encapsulated within an open-end hollow carbon nanostructure, the multiple nanorods being composed of a transition metal oxide of formula (B).
[0089] For the purposes of this invention, the term "working electrode" refers to an electrode in an electrochemical cell where the desired electrochemical transformation, in this case oxidation, occurs when electrons are exchanged between the electrode and the electrolyte. The working electrode may be a carbon-based electrode.
[0090] As used herein, the term “counter electrode” refers to an electrode in an electrochemical cell configured to balance the current flowing through the working electrode; that is, the charge flowing through the counter electrode is necessarily of the opposite sign to the charge flowing through the working electrode. The counter electrode may be a platinum (Pt) electrode or a carbon-based electrode.
[0091] Non-limiting examples of carbon-based electrodes include electrodes made of glassy carbon, pyrolytic carbon films, graphene, carbon black, carbon particles, carbon nanotubes, and graphite.
[0092] As used herein, the term “reference electrode” refers to a nonpolar electrode having a known and highly reproducible potential. The reference electrode provides a stable reference point from which the voltage of the working electrode is measured. Specifically, the reference electrode may include an Ag / AgCl electrode or a reversible hydrogen electrode (RHE).
[0093] According to one embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, the working electrode is a carbon-based electrode, more specifically a glassy carbon electrode.
[0094] In another embodiment, the counter electrode is selected from platinum electrodes and carbon-based electrodes, more specifically platinum electrodes, in combination with one or more features of the various embodiments described above or below, as may be chosen throughout the entire description.
[0095] In another embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, the reference electrode is selected from an Ag / AgCl electrode and a reversible hydrogen electrode (RHE).
[0096] In step i) of the electrochemical process, the conductive surface may be a glassy carbon electrode, a foam, a cloth, a bucky paper, or indium tin oxide (ITO).
[0097] According to one embodiment, the working electrode 1 cm is optionally combined with one or more features of the various embodiments described above or below throughout the entire description. 2 Each portion is coated with 14 μg of precursor material.
[0098] In another embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, a suspension of the precursor material in a suitable solvent is used in step i). The solvent may be, for example, hexane, ethanol, methanol, isopropanol, deionized water, dimethylformamide (DMF), or pentane, among others.
[0099] Electrochemical processes are generally carried out at room temperature in the presence of an electrolyte, which may be an alkali metal or alkaline earth metal halide salt, or an alkali metal or alkaline earth metal hydroxide.
[0100] Non-limiting examples of alkali metal or alkaline earth metal halide salts that can be used include sodium chloride, potassium chloride or lithium chloride, calcium chloride or magnesium chloride. Non-limiting examples of alkali metal hydroxides or alkaline earth metal hydroxides that can be used include sodium hydroxide, potassium hydroxide or lithium hydroxide, calcium hydroxide or magnesium hydroxide.
[0101] According to one embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, the electrolyte is an alkali metal or alkaline earth metal, particularly a chloride salt of KCl, at a concentration of 1 M or more, more specifically 1 to 3 M, more specifically 1.5 to 2.5 M, and even more specifically about 2 M.
[0102] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, the electrolyte is an alkali metal or alkaline earth metal hydroxide, particularly KOH, at a concentration of 0.1 M or higher, more specifically 0.1 to 2 M, more specifically 0.5 to 1.5 M, and even more specifically about 1 M.
[0103] In the electrochemical process of the present invention, formula A z M' 2y Mn 1-xA transition metal oxide of O2(A) can be formed, wherein A is an alkali metal or alkaline earth metal ion of a halide or hydroxide salt, and z is different from 0.
[0104] According to one embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout the entire description, the formula R t M''' 3-t The process is carried out using spherical nanoparticles composed of a transition metal(II,III) oxide represented by O4(C) (wherein t is 0, M''' is Mn, that is, the transition metal(II,III) oxide of formula (C) has the formula Mn3O4), and when an alkali metal halide salt or alkali metal hydroxide is used as the electrolyte, the resulting nanorods are composed of a mixture of transition metal oxides having the formula of formula (A). More specifically, the plurality of nanorods have the formula M' 2y Mn 1-x’ It is composed of a mixture of a metal oxide of O2(A1) and a metal oxide of formula A z’ M' 2y Mn 1-x” It is composed of a mixture with the metal oxide of O2(A2), wherein x'=y and x"=(z' / 4+y), y=0 and 0<z'<4, A is a monovalent metal, manganese can either be in the (IV) oxidation state or a mixture of (IV) and (III), the latter case exhibiting oxygen vacancies, that is, the plurality of nanorods are composed of a metal oxide of formula MnO2(A1) and a metal oxide of formula A z’ Mn 1-x” It is composed of a mixture with the metal oxide of O2(A2), wherein x"=z' / 4 and 0<z'<4.
[0105] In another embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout the entire description, the formula R t M''' 3-t A transition metal(II,III) oxide represented by O4(C) (wherein t is different from 0, M''' is Mn, that is, the transition metal(II,III) oxide of formula (C) is R t Mn 3-thaving the formula O4) are used to carry out the process, and an alkali metal halide salt or an alkali metal hydroxide is used as the electrolyte, the resulting nanorods are composed of a mixture of one or more transition metal oxides having the formula of Formula (A). More specifically, the plurality of nanorods have the formula M' 2y Mn 1-x’ A metal oxide of O2(A1), and a formula A z’ M' 2y Mn 1-x” It is composed of a mixture with a metal oxide of O2(A2), wherein M' is a transition metal other than Mn in a divalent oxidation state, x' is equal to y, x"=(z' / 4+y), 0<y<1 and 0<z'<4, A is a monovalent metal, manganese can assume either the oxidation state (IV) or a mixture of (IV) and (III), and the latter case exhibits oxygen vacancies.
[0106] The electrosynthesis can be carried out in two different ways: iia) applying 1000 to 5000 constant current cycles in the range of -0.2 to 0.8 V at a current density of 0.5 to 5 A per gram of the precursor material, or iib) applying 1000 to 5000 potentiodynamic cycles in the range of 1 to 1.7 V at a scan rate of 40 to 400 mV / s.
[0107] Electrosynthesis can be carried out in two different ways by applying iia) constant current cycles in which the current is kept constant, or alternatively, iib) potentiodynamic cycles in which the potential changes at a constant rate (potential sweep rate) by varying the current.
[0108] According to one embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout the entire description, the process comprises applying 1000 to 5000 constant current cycles, more specifically 1500 to 3500 cycles, even more specifically about 2500 constant current cycles.
[0109] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, in step iia) of the process, the current density is 0.5 to 5 A per gram of precursor material, more specifically 0.7 to 1.3 A per gram of precursor material, and even more specifically about 1 A per gram of precursor material.
[0110] According to another embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, the process includes applying 1,000 to 5,000 cycles, more specifically 1,500 to 3,500 cycles, and even more specifically about 2,500 cycles of potential-dynamic cycles.
[0111] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, in step iia) of the process, the current density is 40 to 400 mV / s, more specifically 100 to 300 mV / s, and even more specifically about 200 mV / s.
[0112] Furthermore, a material that forms part of the present invention includes a plurality of nanorods encapsulated within an open-end hollow carbon nanostructure, wherein the plurality of nanorods are a) Formula A as defined herein z M' 2y Mn 1-x O2(A) transition metal oxides, or b) Formula M” as defined herein 3m / n M 2-m It is composed of O3(B) transition metal oxides. These can be obtained through the following process, which is: i) Formula R as defined herein t M"' 3-t The step of providing a modifying electrode by coating a conductive surface with a precursor material comprising multiple spherical nanoparticles encapsulated within open-end hollow carbon nanostructures, which are composed of O4(C) transition metal (II,III) oxides. ii) Using the counter electrode, reference electrode, and the modifying electrode obtained in step i), electrosynthesis of an aqueous solution containing an electrolyte selected from the group consisting of alkali or alkaline earth metal halide salts or alkali or alkaline earth metal hydroxides is performed. iia) A step of applying a constant current cycle of 5000 or less cycles in the range of -0.2 to 0.8 V with a current density of 0.5 A or more per g of precursor material, or iib) The step of applying 5000 or fewer dynamic cycles in the range of 1 to 1.7V at a scanning speed of 40mV / s or more, In the precursor material of formula (C), when M''' is manganese, a material is obtained that contains multiple nanorods encapsulated within an open-end hollow carbon nanostructure, the multiple nanorods being composed of a transition metal oxide of formula (A). In the precursor material of formula (C), when M''' is a transition metal selected from the group consisting of iron, cobalt, and nickel, a material is obtained that contains multiple nanorods encapsulated within an open-end hollow carbon nanostructure, the multiple nanorods being composed of a transition metal oxide of formula (B).
[0113] All embodiments of the electrochemical processes for preparing the materials of the present invention referred herein also apply to materials obtained by these processes.
[0114] A third aspect of the present invention relates to a precursor material from which the material of the present invention can be obtained. The precursor material comprises a plurality of spherical nanoparticles composed of a transition metal (II,III) oxide of formula (C), R t M"' 3-t O4 (C) The spherical nanoparticles are encapsulated within open-end hollow carbon nanostructures, in the formula, M''' is a transition metal selected from the group consisting of manganese, iron, cobalt, and nickel in divalent and trivalent oxidation states. R is a transition metal other than M''' in the divalent oxidation state. t is a value between 0 and 1, and is greater than or equal to 0. The transition metal oxide in formula (C) is present in an amount of 20-60% of the total weight of the material. The volume of spherical nanoparticles encapsulated within the hollow carbon nanostructure is 50% or less of the total cavity volume of the hollow carbon nanostructure. In particular, the hollow carbon nanostructure is tubular, and its inner diameter is at least twice the average diameter of the spherical nanoparticles.
[0115] In one embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, the present invention relates to a precursor material comprising a plurality of spherical nanoparticles composed of a transition metal (II,III) oxide of formula (C) encapsulated within open-end hollow carbon nanostructures as defined herein.
[0116] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, in a transition metal (II,III) oxide of formula (C), M''' is manganese.
[0117] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, in a transition metal (II,III) oxide of formula (C), M''' is iron.
[0118] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, in a transition metal (II,III) oxide of formula (C), M''' is cobalt.
[0119] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, in a transition metal (II,III) oxide of formula (C), M''' is nickel.
[0120] The precursor materials also include undoped and doped materials with respect to the transition metal (II,III) oxide of formula (C). According to one embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, the transition metal (II,III) oxide of formula (C) is undoped, i.e., t is 0.
[0121] In another embodiment, a transition metal (II,III) oxide is doped, in combination with one or more features of the various embodiments described above or below, as may be optional throughout the entire description, i.e., in the transition metal (II,III) oxide of formula (C), t is greater than 0 and less than 1, and R is a transition metal other than M''' having a divalent oxidation state. More specifically, R is manganese, iron, cobalt, nickel, copper, chromium, molybdenum, titanium, vanadium, etc. R is selected from the group consisting of iron, cobalt, and nickel. More specifically, R is selected from the group consisting of iron, cobalt, and nickel. In a more specific embodiment, t is 0.01 to 0.4, and more specifically, t is 0.05 to 0.09. More specifically, t is about 0.01, about 0.02, about 0.03, about 0.05, about 0.07, about 0.09, about 0.1, about 0.15, about 0.20, about 0.25, about 0.3, about 0.35, or about 0.4.
[0122] All embodiments of the present invention relating to hollow carbon nanostructures are also applicable to precursor materials.
[0123] The precursor material comprises spherical nanoparticles. For the purposes of this invention, the term “spherical” nanoparticles refers to any shape that is perfectly spherical or nearly spherical. Spherical nanoparticles are characterized by a diameter, which refers to the length passing through the midpoint of the nanoparticle from surface edge to surface edge. The diameter can be measured by methods well known in the art, such as a transmission electron microscope (TEM). The term “average diameter” typically refers to the average value obtained from 80 different diameter measurements.
[0124] In one embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, the spherical nanoparticles have an average diameter of 2 to 20 nm, more specifically 7 to 15 nm, and even more specifically about 10 ± 2 nm. In another embodiment, the spherical nanoparticles have an average diameter of about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, about 10 nm, about 11 nm, about 12 nm, about 13 nm, about 14 nm, about 15 nm, about 16 nm, about 17 nm, about 18 nm, about 19 nm, and about 20 nm.
[0125] In another embodiment, the spherical nanoparticles are 50-5000 nm in size, optionally combined with one or more features of the various embodiments described above or below throughout this description. 2 More specifically, 600-2800nm 2 More specifically, 800-1800nm 2 It has a surface area of [value].
[0126] The precursor material can be prepared by a process defined in the fourth embodiment, which is a) Providing a mixture of a transition metal(II) salt and optionally a second salt of a transition metal other than a first transition metal having a divalent oxidation state, in the presence of a surfactant in a suitable solvent, wherein the metal of the first transition metal(II) salt is selected from manganese, iron, and cobalt, and the metal of the second salt is other than the metal of the first salt; b) Adding the mixture from step a) to a suspension of hollow carbon nanostructures in a suitable solvent, c) The step of heating the suspension to a temperature of 80-110°C, d) Add water to the suspension from step c) and heat to a temperature of 80-110°C to obtain a precursor material of formula (C), and the process includes the steps of: When step a) is carried out in the absence of another salt of the transition metal, the material of formula (C) is obtained, where t is 0. When step a) is carried out in the presence of a second salt of the transition metal, the precursor material of formula (C) is obtained, where t is different from 0, and R is a transition metal other than M''' in the divalent oxidation state.
[0127] The above process has the advantage of being able to be carried out under ambient conditions (room temperature and atmospheric pressure (approximately 1,013.25 hPa)). Furthermore, this process can be carried out in the presence of water.
[0128] Step (a) is carried out in the presence of a surfactant. Non-limiting examples of surfactants that may be used include (C1-C) oleic acid, lauric acid, stearic acid, myristic acid and hexadecanoic acid. 20 ) Acids such as alkylcarboxylic acids, oleylamine, laurylamine, hexadecylamine, trioctylamine and dioctylamine (C1-C 20 Examples include alkylamines or mixtures thereof.
[0129] In one embodiment, optionally combined with one or more features of the various embodiments described above or below throughout the entire description, the metal:surfactant molar ratio is 1:8 to 1:14, particularly 1:10 to 1:12.
[0130] For the purpose of the present invention, "(C1-C n The term "alkyl" refers to a linear or branched saturated hydrocarbon group having 1 to n carbon atoms. Examples include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl or tert-butyl, n-pentyl or n-hexyl groups, etc.
[0131] According to one embodiment, the surfactant may be combined with one or more features of the various embodiments described above or below, as may be described throughout the entire description, to be (C1-C 20) an alkylamine, more specifically selected from the group consisting of oleylamine, laurylamine, hexadecylamine, trioctylamine, dioctylamine and mixtures thereof.
[0132] Non-limiting examples of salts that may be used in step a) include nitrates, sulfates, chlorides, or acetates. When a second salt is present, the anions of the salts may be the same or different.
[0133] According to one embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, the transition metal(II) salt of step (a) is selected from the group consisting of nitrates, sulfates, chlorides, and acetates, more specifically an acetate.
[0134] In another embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, the salt of the second transition metal having a divalent oxidation state is selected from the group consisting of nitrates, sulfates, manganese salts, chloride salts, and acetate salts, more specifically acetate salts.
[0135] Step a) is generally carried out at room temperature and in a suitable solvent. Non-limiting examples of solvents that can be used include (C6) aromatic solvents, such as xylene, benzene, toluene, fluorobenzene, chlorobenzene, iodobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, and 1,2,3-triiodobenzene. Examples include 1,2,4-triiodobenzene, fluorotoluene, 1,2-difluorotoluene, 1,3-difluorotoluene, 1,4-difluorotoluene, 1,2,3-trifluorotoluene, 1,2,4-trifluorotoluene, chlorotoluene, 1,2-dichlorotoluene, 1,3-dichlorotoluene, 1,4-dichlorotoluene, 1,2,3-trichlorotoluene, 1,2,4-trichlorotoluene, iodotoluene, 1,2-diiodotoluene, 1,3-diiodotoluene, 1,4-diiodotoluene, 1,2,3-triiodotoluene, 1,2,4-triiodotoluene, or combinations thereof.
[0136] In one embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, the solvent used in step a) is a (C6) aromatic solvent, more specifically xylene.
[0137] The solvent used in step (b) may be the same as or different from the solvent used in step (a).
[0138] In one embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, the solvent used in step b) is the solvent used in step a).
[0139] In another embodiment, optionally combined with one or more features of the various embodiments described above or below throughout this description, the solvent used in step b) is a (C6) aromatic solvent, more specifically xylene.
[0140] Step c) includes heating the solution obtained in step b) to a temperature of 80–110°C to obtain the material of formula (C). A convenient temperature gradient, for example, 1–10°C / min, more specifically about 5°C / min, can be used.
[0141] In one embodiment, the temperature used in step c) is 80 to 110°C, more specifically about 90°C, optionally combined with one or more features of the various embodiments described above or below throughout the entire description.
[0142] After step c), water may be added at the same temperature as in step c), while stirring particularly vigorously.
[0143] The precursor material can be isolated, in particular, by centrifugation at room temperature (e.g., 6,000 to 10,000 rpm for 5 to 15 minutes), followed by filtration using, for example, a polytetrafluoroethylene (PTFE) membrane filter (pore size 0.45 μm, diameter 47 mm), and then washed with one or more solvents such as hexane, ethanol, acetone, or a mixture thereof.
[0144] Optionally, the obtained precursor material can be resuspended in a suitable solvent such as hexane for, for example, 10 to 30 minutes, sonicated, and filtered again to remove nanoparticles from the outer surface of the hollow carbon nanostructure.
[0145] Optionally, in the obtained precursor material, the organic cap layer (i.e., surfactant) can be removed from the nanoparticle surface by heating at a temperature of at least 300°C.
[0146] In one embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, the solvent used in step b) is the solvent used in step a).
[0147] According to another embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, the present invention relates to a process for preparing a precursor material as defined above, wherein the process is a) Providing a mixture of a transition metal(II) salt and optionally a second salt of a transition metal other than a first transition metal having a divalent oxidation state, in the presence of a surfactant in a suitable solvent, wherein the metal of the first transition metal(II) salt is selected from manganese, iron, and cobalt, and the metal of the second salt is other than the metal of the first salt; b) Adding the mixture from step a) to a suspension of hollow carbon nanostructures in a suitable solvent, c) The step of heating the suspension to a temperature of 80-110°C, d) Add water to the suspension from step c) and heat to a temperature of 80-110°C to obtain the precursor material of formula (C), e) Optionally, the material obtained in step c) is isolated by centrifugation, particularly at 6,000 to 10,000 rpm for 5 to 15 minutes, particularly at room temperature, followed by filtration. f) Optionally, the isolated material from step d) is washed with one or more solvents selected from the group consisting of hexane, ethanol, acetone and mixtures thereof. g) Optionally, the obtained precursor material is resuspended in a suitable solvent for 10-30 minutes and sonicated, and the precursor material is filtered to remove nanoparticles from the outer surface of the hollow carbon nanostructure. h) optionally includes the step of removing the organic cap layer (i.e., surfactant) from the surface of the nanoparticles by heating at a temperature of at least 300°C.
[0148] Furthermore, examples of elements forming part of the present invention include formula R as defined herein.t M"' 3-t This precursor material is composed of O4(C) transition metal (II,III) oxides and contains multiple spherical nanoparticles encapsulated within open-end hollow carbon nanostructures. a) Providing a mixture of a transition metal(II) salt and optionally a second salt of a transition metal other than a first transition metal having a divalent oxidation state, in the presence of a surfactant in a suitable solvent, wherein the metal of the first transition metal(II) salt is selected from manganese, iron, and cobalt, and the metal of the second salt is other than the metal of the first salt; b) Adding the mixture from step a) to a suspension of open-end hollow carbon nanostructures in a suitable solvent, c) The step of heating the suspension to a temperature of 80-110°C, d) Add water to the suspension from step c) and heat to a temperature of 80-110°C to obtain a precursor material of formula (C), obtained by a process comprising the steps of, When step a) is carried out in the absence of another salt of the transition metal, the material of formula (C) is obtained (where t is 0), and when step a) is carried out in the presence of a second salt of the transition metal, the precursor material of formula (C) is obtained (where t is different from 0, and R is a transition metal other than M''' in the divalent oxidation state).
[0149] All embodiments of the electrochemical process for preparing the precursor material of the present invention described herein are also applicable to the precursor material obtained by this process.
[0150] According to another embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout this description, the present invention relates to a process for preparing a material comprising a plurality of nanorods composed of transition metal oxides as defined above, wherein the process is a) Providing a mixture of a transition metal(II) salt and optionally a second salt of a transition metal other than a first transition metal having a divalent oxidation state, in the presence of a surfactant in a suitable solvent, wherein the metal of the first transition metal(II) salt is selected from manganese, iron, and cobalt, and the metal of the second salt is other than the metal of the first salt; b) Adding the mixture from step a) to a suspension of open-end hollow carbon nanostructures in a suitable solvent, c) The step of heating the suspension to a temperature of 80-110°C, d) Add water to the suspension from step c) and heat to a temperature of 80-110°C to obtain a precursor material of formula (C), When step a) is carried out in the absence of another salt of the transition metal, the material of formula (C) is obtained (where t is 0), and when step a) is carried out in the presence of a second salt of the transition metal, the precursor material of formula (C) is obtained (where t is different from 0, and R is a transition metal other than M''' in the divalent oxidation state), and step, i) A step of providing a modifying electrode by coating a conductor with the precursor material obtained in step c), ii) Using the counter electrode, reference electrode, and reforming electrode obtained in step i), electrosynthesis of an aqueous solution containing an electrolyte selected from the group consisting of an alkali or alkaline earth metal chloride salt at a concentration of 1 M or more and an alkali or alkaline earth metal hydroxide at a concentration of 0.1 M or more, iia) Apply a constant current cycle of 5000 or fewer cycles in the range of -0.2 to 0.8 V with a current density of 0.5 A or more per g of precursor material, or iib) The step of applying 5000 or fewer dynamic cycles in the range of 1 to 1.7V at a scanning speed of 40mV / s or more, In the precursor material of formula (C), when M''' is manganese, a material is obtained that contains multiple nanorods encapsulated within an open-end hollow carbon nanostructure, the multiple nanorods being composed of a transition metal oxide of formula (A). In the precursor material of formula (C), when M''' is a transition metal selected from the group consisting of iron, cobalt, and nickel, a material is obtained that contains multiple nanorods encapsulated within an open-end hollow carbon nanostructure, the multiple nanorods being composed of a transition metal oxide of formula (B).
[0151] This also includes the previously defined materials, which can be obtained by a process comprising steps a), b), c), i), ii) and iii) as defined herein.
[0152] As described above, the material of the present invention has applications not only in the field of energy storage in batteries, but also in the field of energy conversion as the cathode and anode of water splitting in fuel cells, where the reduction reaction of oxygen to water and the oxidation of water to oxygen are involved, respectively, and it also has applications as an electrode catalyst.
[0153] Accordingly, another aspect of the present invention relates to the use of a material comprising a plurality of nanorods made of transition metal oxides as defined above as an electrode catalyst. According to one embodiment, optionally in combination with one or more features of the various embodiments described above or below throughout the entire description, the present invention relates to the use of the material defined above as an electrode catalyst, as a cathode of a fuel cell, or as an anode of a water splitter.
[0154] Throughout the specification and claims, the word “comprise” and variations thereof are not intended to exclude other technical features, additives, components, or steps. Furthermore, the word “comprise” encompasses the case of “consisting of.” Further objects, advantages, and features of the present invention may become apparent to those skilled in the art upon examination of the specification or may be acquired through the practice of the invention. The following examples and drawings are provided for illustrative purposes only and are not intended to limit the invention. Furthermore, the present invention encompasses all possible combinations of the specific embodiments and preferred embodiments described herein.
[0155] Examples Materials: Carbon nanofibers (CNF) manufactured by chemical vapor deposition were purchased from Pyrograph Products (outer diameter 110±30 nm, inner diameter 70±20 nm). In this test, both initial carbon nanofibers and pulverized carbon nanofibers were used, so the length of the nanofibers ranged from 10 (initial state) to 2 (pulverized) μm.
[0156] Grinding of carbon nanofibers was performed by mechanical ball milling using a Retsch MM400 ball mill (600 rpm). In a typical experiment, 50 mg of CNF was placed in a stainless steel container (5 mL) equipped with stainless steel balls (10 mm in diameter) and ground in air at 600 rpm (98% yield) for 180 minutes. No further purification steps were required. To produce graphitized carbon nanofibers, the ground carbon nanofibers (CNF, 100 mg) were placed in an alumina crucible and heated under an argon atmosphere. The sample was first purged at room temperature for 30 minutes, then heated to 1000°C at a rate of 10°C / min, held for 90 minutes, and then cooled under an argon atmosphere. All other reagents were purchased from Sigma-Aldrich and used without further purification.
[0157] Hollow carbon nanofiber (rA z M' 2y Mn1-x O2@CNF or r-M" 3m / n M 2-m O3@CNF), the synthesis of undoped or doped nanorods therein is carried out in the following two steps: synthesis of s-R t M''' 3-t O4NPs inside CNF, followed by electrochemical synthesis.
[0158] TEM was performed on a JEOL JEM F200 microscope equipped with a cold field emission gun (Cold-FEG) operating at 200 kV using an ultra-high resolution pole piece. TEM images were acquired using a Gatan OneView camera. Energy-dispersive X-ray spectroscopy (EDS) was performed using a Centurio Large Angle Silicon Drift Detector (SDD) that collects X-rays from a detection area of 100 mm 2 . TEM test specimens were prepared by casting several drops of a suspension of the carbon material in hexane onto a "holey" carbon film mounted on a copper grid before drying under a nitrogen flow. Thermogravimetric analysis (TGA) was performed using a TGA / DSC 3+ Mettler Toledo apparatus in air over the range of 25 to 1000°C at a scanning rate of 5°C / min. Raman spectral analysis was performed using a RENISHAW Raman microscope equipped with an Ar ion laser (514 nm). Powder X-ray diffraction (XRD) patterns were recorded using a PANalytical diffractometer equipped with a CuKα source (λ=1.5418 Å). Data were analyzed and processed using the X'Pert Data software package.
[0159] Example 1 In-situ synthesis of s-R t M''' 3-t O4NPs inside CNF (s-R t M''' 3-t O4@CNF) In a typical experiment, a mixture of manganese(II) acetate (1.1 mmol, 190.3 mg) and oleylamine (12.2 mmol, 5.1 mL ratio of metal (Mn):surfactant 1:11.1) in xylene (7 mL) was added to a suspension of carbon nanofibers (CNF, 25 mg) that had been pre-treated with xylene (10 mL) for 15 minutes. t M"' 3-t To obtain Mn3O4 nanoparticles doped within O4@CNF, 15% (mmol) of manganese(II) acetate was replaced with iron(II) acetate, cobalt(II) acetate, or nickel(II) acetate, respectively. Specifically, a solution containing manganese(II) acetate (0.935 mmol) in xylene (7 mL) and optionally iron(II) acetate, cobalt(II) acetate, or nickel(II) acetate (0.165 mmol), oleylamine (12.2 mmol, 5.1 mL), and a metal (Mn+Fe or Mn+Co or Mn+Ni):surfactant ratio of 1:11.1 was added to a suspension of CNF (25 mg) in xylene (10 mL). In all cases, the solution was heated to 90°C at 5°C / min in air. Deionized water (1 mL) was added to the dark-colored suspension at 90°C with vigorous stirring, and the resulting suspension was aged at 90°C in air for 3 hours. Hybrid materials (s-Mn3O4@CNF or sR when iron(II) acetate, cobalt(II) acetate, or nickel(II) acetate is added) t Mn 3-tO4@CNF) was isolated by centrifugation at room temperature (8000 rpm, 10 min), filtered through a PTFE (polytetrafluoroethylene) membrane filter (pore size 0.45 μm, diameter 47 mm), and then thoroughly washed with hexane (50 mL), ethanol (50 mL), and finally acetone (25 mL) to obtain a dark black solid. Furthermore, the obtained solid was resuspended and sonicated in hexane (25 mL) for 15 minutes, and filtered again to remove nanoparticles from the outer surface of the carbon nanofibers (CNF). The obtained black solid was heated in a furnace at 300 °C in air for 2 hours to remove the organic capping layer (i.e., surfactant) from the nanoparticle surface, resulting in undoped (s-Mn3O4@CNF, Figure 1) or cobalt (s-Co / Mn3O4@CNF, Co 0.15 Mn 2.85 O4@CNF, Figure 7), Nickel (s-Ni / Mn3O4@CNF, Ni 0.15 Mn 2.85 O4@CNF, Figure 8), or iron (s-Fe / Mn3O4@CNF, Fe 0.15 Mn 2.85 O4@CNF, Figure 9) doped nanoparticles (sR t Mn 3-t A dark black solid containing O4@CNF was obtained.
[0160] Figure 3 shows the Raman spectra of s-Mn3O4@CNF(a), s-Co / Mn3O4@CNF(b), s-Ni / Mn3O4@CNF(c), and s-Fe / Mn3O4@CNF(d). In all cases, Mn3O4 (i.e., 660 cm⁻¹) -1 A band related to ) was observed, confirming that the replacement of Mn atoms with Co, Ni, or Fe (i.e., doping) does not affect the crystal structure.
[0161] Figure 4 shows the X-ray powder diffraction patterns for s-Mn3O4@CNF(a), s-Co / Mn3O4@CNF(b), s-Ni / Mn3O4@CNF(c), and s-Fe / Mn3O4@CNF(d). In all cases, a peak associated with Mn3O4 (i.e., strongest around 36.2°) was observed, confirming that the exchange of Mn atoms with Co, Ni, or Fe (i.e., doping) does not affect the crystal structure. The peak at 26.4° corresponds to carbon nanofibers.
[0162] Figure 5 shows the TGA measurements for (a) s-Mn3O4@CNF, (b) s-Co / Mn3O4@CNF, (c) s-Ni / Mn3O4@CNF, and (d) s-Fe / Mn3O4@CNF. Stepwise oxidation of the CNF structure occurs in the same range (i.e., 400-600°C) for all materials, but the metal oxide content in the hybrid (L) after annealing at 1000°C varies from 13-30%.
[0163] Figure 6 shows histograms of the nanoparticle size distribution for (a) s-Mn3O4@CNF, (b) s-Co / Mn3O4@CNF, (c) s-Ni / Mn3O4@CNF, and (d) s-Fe / Mn3O4@CNF. It can be seen that doping Mn3O4 with Ni or Fe does not change the nanoparticle size as much as doping with Co atoms. Furthermore, Figure 10 shows that incorporating cobalt, nickel, or iron atoms into the crystalline structure of manganese oxide alters the oxidation and reduction potential of manganese.
[0164] Further experiments will demonstrate the scalability of the synthesis procedure by increasing the amount of reagents, for example, by a tenfold.
[0165] By replacing 5%, 10%, 15%, and 20% mmol of manganese(II) acetate with cobalt(II) acetate, Mn3O4 nanoparticles (sR) doped inside CNF can be incorporated. t Mn 3-tFurther experiments were conducted to obtain O4@CNF (t 0.05~0.20). Similar materials were found to be obtainable. Nevertheless, doping exceeding 15% (t>0.15) reduces the metal oxide loading in the hybrid material (Figure 21).
[0166] Example 2 sR within graphitized carbon nanostructures t Mn 3-t In-situ synthesis of O4NP sR within graphitized carbon nanostructures t Mn 3-t O4NPs were obtained using the same procedure as in Example 1, but this time the initial carbon nanofibers were replaced with graphitized carbon nanofibers. The obtained material was found to be similar to the material in Example 1 (no change in the composition and morphology of the NPs based on characterization by powder X-ray diffraction, thermogravimetric analysis, Raman spectroscopy, and transmission electron microscopy). More importantly, electrochemical impedance spectroscopy of the obtained material revealed a slight increase of 10–22 Ω (known as solution resistance) between the electrode surface and the electrolyte compared to the material in Example 1. Such an increase supports the increased hydrophobicity of the material when graphitized carbon nanofibers are used, without affecting the electrocatalytic performance of the NPs.
[0167] Example 3 In situ synthesis of s-Co3O4NP (s-Co3O4@CNF) within CNF s-Co3O4 nanoparticles inside CNF were obtained following the same protocol as described in Example 1, but with the use of cobalt(II) acetate instead of manganese(II) acetate.
[0168] The Raman spectrum of s-Co3O4@CNF is shown in Figure 3(e). The band associated with Co3O4 is 685.3 cm⁻¹. -1 It was observed.
[0169] The powder X-ray diffractogram of s-Co3O4@CNF is shown in Figure 4(e). Peaks associated with Co3O4 were observed at 36.9, 31.3, 59.5, and 44.9°.
[0170] The TGA plot of s-Co3O4@CNF is shown in Figure 5(e). Stepwise oxidation of the CNF structure occurs between 350 and 600°C, and the metal oxide content (L, load) in the hybrid is 67%.
[0171] The nanoparticle size distribution histogram of s-Co3O4@CNF is shown in Figure 6(d), which shows an average size of 15±5 nm.
[0172] Example 4 In situ synthesis of s-Fe3O4NP (s-Fe3O4@CNF) within CNF s-Fe3O4 nanoparticles inside CNF were obtained following the same protocol as described in Example 1, but with iron(II) acetate instead of manganese(II) acetate.
[0173] The Raman spectrum of s-Fe3O4@CNF is shown in Figure 3(f). The bands associated with Fe3O4 are 221, 286, and 397 cm⁻¹. -1 It was observed.
[0174] The powder X-ray diffractogram of s-Fe3O4@CNF is shown in Figure 4(f). The strongest peak associated with Fe3O4 was observed at 35.7°.
[0175] The TGA plot of s-Fe3O4@CNF is shown in Figure 5(f). Slow oxidation of the CNF structure occurs between 400 and 650°C, and the metal oxide content (L, load) in the hybrid is 40%.
[0176] The nanoparticle size distribution histogram of s-Fe3O4@CNF is shown in Figure 6(e), which shows an average size of 7±2 nm.
[0177] Additional experiments were conducted to obtain s-Fe3O4@CNF by changing the metal / oleylamine ratio to 1:0.9 and 1:0.75. It was found that reducing the amount of surfactant did not significantly increase the size of NPs.
[0178] Example 5 rA z M' 2y Mn 1-x O2@CNF and rM” 3m / n M 2-m Electrosynthesis of O3@CNF All electrochemical tests were performed at room temperature using a conventional three-electrode cell in an electrochemical station (Autolab PGSTAT302N), and electrochemical synthesis was performed using an electrochemical station (Autolab 201A). Ag / AgCl and reversible hydrogen electrodes (RHE) were used as reference electrodes, and carbon rods were used as counter electrodes. Sample-coated glassy carbon electrodes (GCE) and rotating ring disk electrodes (RRDE) were used as working electrodes. Catalyst inks (s-Mn3O4@CNF, Fe3O4@CNF, or sR) were used. 0.15 Mn 2.85 The modifying electrode was prepared by dropping 5 μL of O4@CNF (R=Co, Ni, or Fe) onto a GCE (3 mm diameter) or 10 μL onto an RRDE (5 mm diameter) and allowing it to air dry. This process was performed with a catalyst mass loading of 0.1 mg / cm³ on the RRDE. 2 The activated catalyst and GCE contain 0.01 mg / cm³ 2The process was repeated until the desired result was reached. Before use, the GCE and RRDE were mechanically polished with an aqueous slurry of alumina powder (0.05 μm), rinsed with Milli-Q water and acetone, and dried under nitrogen. The catalyst ink for coating the RRDE was prepared by ultrasonically dispersing the catalyst (2 mg) in a mixed solution consisting of ethanol (980 μL) and Nafion solution (20 μL, 0.5 wt%). The catalyst ink for coating the GCE was prepared by ultrasonically dispersing the catalyst (1 mg) in hexane (1 mL). Cyclic voltammogram (CV) measurements were performed in N2-saturated 2 M KCl at a scanning speed of 50 mV / s. Linear sweep voltammetry (LSV) measurements for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) were performed in O2-saturated 1 M KOH with a scanning speed of 10 mV / s at a rotation speed of 1600 rpm. Several constant current or potential-dynamic cycles (i.e., 2500) were performed at either a high current density (i.e., 1 A / g) or a high scanning speed (i.e., 200 mV / s) at -0.2 to 0.8 V (vs Ag / AgCl) in KCl (2M) or 1 to 1.7 V (vs RHE) in KOH (1M). Under these conditions, based on the dissolution-precipitation mechanism, undoped (rK / MnO2@CNF, Figure 2 and r-Fe2O3@CNF, Figure 22) or nanorods doped with cobalt (r-KCo / MnO2@CNF, Figure 18), nickel (r-KNi / MnO2@CNF, Figure 19), or iron (r-KFe / MnO2@CNF, Figure 20) were obtained.
[0179] To support the morphological transformation, TEM images of s-Mn3O4@CNF were taken after several charge and discharge cycles in 2M KCl (Figure 14). Electrochemical treatment induced aggregation of nanoparticles (see Figure 1 for a comparison before treatment), which appears to be a preliminary phase for achieving complete morphological transformation. This demonstrates that confinement provides high stability without inhibiting the intrinsic reactivity of the nanoparticles.
[0180] Furthermore, the constant current charging and discharging cycles of manganese oxide nanoparticles in carbon nanofibers before (s-Mn3O4@CNF, dotted solid line) and after (r-MnO2@CNF, dashed line) a 2500-cycle electrosynthesis in 2M KCl (in Figure 15(a), the solid black line represents carbon nanofibers without manganese oxide), as well as the change in capacitance during the stability cycle (Figure 15(b)), show a large (more than 4-fold) increase in capacitance associated with the formation of nanorods within the carbon nanofibers, meaning that the nanorods have a larger surface area than the spherical nanoparticles.
[0181] The electrocatalytic performance of manganese oxide nanoparticles in undoped (s-Mn3O4@CNF) and cobalt-doped (s-Co / Mn3O4@CNF), nickel-doped (s-Ni / Mn3O4@CNF), and iron-doped (s-Fe / Mn3O4@CNF) carbon nanofibers was evaluated using linear sweep voltammograms (LSV, Figure 11) in oxygen-saturated KOH (1M) solution at room temperature. It was observed that incorporating cobalt, nickel, and iron atoms into the Mn3O4 crystal structure increased catalytic activity in both oxygen reduction (ORR, in the potential range below 1V, inset) and water oxidation (OER, in the potential range above 1.4V).
[0182] The electrocatalytic activity of the nanomaterials of the present invention was also measured by linear scanning voltammetry of manganese oxide nanoparticles on carbon nanofibers in an alkaline solution of 1 M KOH saturated with oxygen before (s-Mn3O4@CNF, solid line) and after (r-MnO2@CNF, dotted line) electrosynthesis (2500 cycles in 2 M KCl) (Figure 16). The change in morphology is understood to have resulted in an increase in catalytic ability to oxidize water (reduction of OER, overpotential) and improved reaction rate (due to a lower Tafel slope).
[0183] In the case of manganese oxide nanoparticles on carbon nanofibers doped with (a) cobalt, (b) nickel, or (c) iron (Figure 17), high electrocatalytic activity is maintained after several cycles (i.e., 2500), while the ability to oxidize water (OER in the potential range above 1.4 V) is significantly improved in the case of s-Ni / Mn3O4@CNF in CNF.
[0184] Finally, to test the stability of the encapsulated manganese oxide nanoparticles, we evaluated manganese oxide nanoparticles (s-Mn3O4) deposited on both the outside and inside of nanofibers (Figure 12(a)). Materials containing nanoparticles deposited on the outside of nanofibers were synthesized in the same manner as s-Mn3O4@CNF without a purification step, leaving nanoparticles on the outside of the nanofibers as well. Materials with nanoparticles deposited on the outside of nanofibers were found to be less stable, with a significant decrease in current after only 500 cycles during electrosynthesis in KCl (Figure 13), which may be related to material loss (nanoparticles adhering to the outside of the nanofibers). TEM images showed only the dissolution of nanoparticles supported on the outside of nanofibers (Figure 12(b)), confirming that nanoparticle encapsulation limits their dissolution.
[0185] For completeness, various aspects of the present invention are described in the following numbered clauses.
[0186] Clause 1. A material comprising a plurality of nanorods encapsulated within an open-end hollow carbon nanostructure, wherein the plurality of nanorods are a) Transition metal oxides of formula (A) A z M' 2y Mn 1-x O2 (A) or, b) Transition metal oxides of formula (B) M" 3m / n M 2-m O3 (B) It consists of one of the following, in the formula, In formula (A), A is a monovalent metal, M' is a transition metal other than Mn in the divalent oxidation state, x is equal to (z / 4+y), 0≦y<1 and 0≦z<4, manganese can take either the oxidation state of (IV) or a mixture of (IV) and (III), and in the latter case, it exhibits oxygen vacancies, In formula (B), M is a transition metal in the trivalent oxidation state selected from iron, cobalt and nickel, M'' is a transition metal equal to or different from M in oxidation state n, n is a value of 2 to 6, and 0≦m<2, The transition metal oxide of formula (A) or formula (B) is present in an amount of 20 to 60% by weight relative to the total weight of the material, A material, wherein the volume of the nanorods encapsulated in the hollow carbon nanostructure is 50% or less relative to the total void volume of the hollow carbon nanostructure.
[0187] Clause 2. The material according to clause 1, wherein in the transition metal oxide of formula (A), y and z are 0, and in the transition metal oxide of formula (B), m is 0.
[0188] Clause 3. The material according to clause 1, wherein in the transition metal oxide of formula (A), at least one of y or z is different from 0, and in the transition metal oxide of formula (B), m is different from 0.
[0189] Clause 4. The plurality of nanorods according to any one of clauses 1 to 3, which are composed of the transition metal (IV) oxide of formula A z M' 2y Mn 1-x O2(A), the material according to any one of clauses 1 to 3.
[0190] Clause 5. The plurality of nanorods according to any one of clauses 1 to 3, which are composed of the transition metal (III) oxide of formula M'' 3m / n M 2-m O3(B), the material according to any one of clauses 1 to 3.
[0191] Clause 6. The material according to clause 5, wherein M is iron.
[0192] Clause 7. The material according to clause 5, wherein M is cobalt.
[0193] Clause 8. The material according to Clause 5, wherein M is nickel.
[0194] Clause 9. The material according to any one of Clauses 1 to 8, wherein the nanorods have an average thickness of 5 to 20 nm and an average length of 16 to 180 nm.
[0195] Clause 10. The nanorods have a surface area of 280 nm 2 or more, the material according to any one of Clauses 1 to 9.
[0196] Clause 11. The material according to any one of Clauses 1 to 10, wherein the amount of the hollow carbon nanostructure in the material is 40 to 80% by weight relative to the total weight of the material.
[0197] Clause 12. The material according to any one of Clauses 1 to 11, wherein the hollow carbon nanostructure is selected from carbon nanotubes, graphitized carbon nanotubes, heteroatom-doped carbon nanotubes, carbon nanofibers, graphitized carbon nanofibers, and heteroatom-doped carbon nanofibers.
[0198] Clause 13. The material according to any one of Clauses 1 to 12, wherein the hollow carbon nanostructure is a hollow tubular carbon nanostructure, in particular a carbon nanotube.
[0199] Clause 14. The material according to Clause 13, wherein the average inner diameter of the hollow tubular carbon nanostructure is at least 2 times, more specifically 2 to 20 times the average thickness of the nanorods.
[0200] Clause 15. The material according to either Clause 13 or 14, wherein the hollow tubular carbon nanostructure has an average inner diameter of 20 to 180 nm, or 30 to 180 nm, or 40 to 100 nm, an average outer diameter of 40 to 200 nm, or 60 to 140 nm, and an average length of 10 μm or less.
[0201] Clause 16. The material according to any one of Clauses 1 to 15, wherein the volume of the nanorods encapsulated within the hollow carbon nanostructure is 10% or less of the total cavity volume of the hollow carbon nanostructure.
[0202] Clause 17. An electrochemical process for preparing the materials defined in Clause 1, i) A step of providing a modifying electrode by coating a conductive surface with a precursor material comprising a plurality of spherical nanoparticles composed of transition metal (II,III) oxides of formula (C), R t M"' 3-t O4 (C) The spherical nanoparticles are encapsulated within an open-end hollow carbon nanostructure, in the formula, M''' is a transition metal selected from the group consisting of manganese, iron, cobalt, and nickel in divalent and trivalent oxidation states. R is a transition metal other than M''' in the divalent oxidation state. t is a value between 0 and 1, The transition metal oxide of formula (C) is present in an amount of 20-60% by weight relative to the total weight of the material. The step is that the volume of the spherical nanoparticles encapsulated within the hollow carbon nanostructure is 50% or less of the total cavity volume of the hollow carbon nanostructure. ii) Using the counter electrode, the reference electrode, and the modifying electrode obtained in step i), electrosynthesis of an aqueous solution containing an electrolyte selected from the group consisting of alkali or alkaline earth metal halide salts or alkali or alkaline earth metal hydroxides is performed. iia) Apply a constant current cycle of 5000 or less cycles in the range of -0.2 to 0.8 V with a current density of 0.5 A or more per g of precursor material, or iib) An electrochemical process comprising the step of applying 5,000 or fewer electrokinetic cycles in the range of 1 to 1.7 V at a scanning speed of 40 mV / s or more.
[0203] Clause 18. The electrochemical process according to Clause 17, wherein in the precursor material of Formula (C), the average inner diameter of the hollow tubular carbon nanostructure is at least 2 times, more specifically 2 to 20 times the average diameter of the spherical nanoparticles.
[0204] Clause 19. A precursor material comprising a plurality of spherical nanoparticles composed of a transition metal (II,III) oxide of Formula (C), R t M''' 3-t O4 wherein the spherical nanoparticles are encapsulated within an open-ended hollow carbon nanostructure, and in the formula, M''' is a transition metal selected from the group consisting of manganese, iron, cobalt, and nickel in divalent and trivalent oxidation states, R is a transition metal other than M''' in the divalent oxidation state, t is a value of 0 or more and less than 1, the transition metal oxide of Formula (C) is present in an amount of 20 to 60% by weight relative to the total weight of the material, and the volume of the spherical nanoparticles encapsulated in the hollow carbon nanostructure is 50% or less relative to the total cavity volume of the hollow carbon nanostructure.
[0205] Clause 20. The precursor material according to Clause 19, wherein M''' is manganese.
[0206] Clause 21. The precursor material according to Clause 19, wherein M''' is iron.
[0207] Clause 22. The precursor material according to Clause 19, wherein M''' is cobalt.
[0208] Clause 23. The precursor material according to Clause 19, wherein M''' is nickel.
[0209] Clause 24. The precursor material according to any one of Clauses 19 to 23, wherein the spherical nanoparticles have an average diameter of 2 to 20 nm.
[0210] Clause 25. The spherical nanoparticles have a size of 50 to 5000 nm 2A precursor material having the surface area of any of the clauses 19 to 24.
[0211] Clause 26. The precursor material according to any one of Clauses 19 to 25, wherein the amount of the hollow carbon nanostructure in the material is 40 to 80% by weight relative to the total weight of the material.
[0212] Clause 27. The precursor material according to any one of Clauses 19 to 26, wherein the hollow carbon nanostructure is selected from carbon nanotubes, graphitized carbon nanotubes, heteroatom-doped carbon nanotubes, carbon nanofibers, graphitized carbon nanofibers, and heteroatom-doped carbon nanofibers.
[0213] Clause 28. The precursor material according to any one of Clauses 19 to 27, wherein the hollow carbon nanostructure is a hollow tubular carbon nanostructure, in particular a carbon nanotube.
[0214] Clause 29. The precursor material according to Clause 28, wherein the inner diameter of the hollow tubular carbon nanostructure is at least twice, more specifically 2 to 20 times, the average diameter of the spherical nanoparticles.
[0215] Clause 30. The precursor material according to either Clause 28 or 29, wherein the hollow tubular carbon nanostructure has an average inner diameter of 20-180 nm, or 30-180 nm, or 40-100 nm, an average outer diameter of 40-200 nm, or 60-140 nm, and an average length of 10 μm or less.
[0216] Clause 31. The precursor material according to any one of Clauses 19 to 30, wherein the volume of spherical nanoparticles encapsulated within the hollow carbon nanostructure is 10% or less of the total cavity volume of the hollow carbon nanostructure.
[0217] Clause 32. A process for preparing the precursor material described in Clause 19, a) Providing a mixture of a transition metal(II) salt and optionally a second salt of a transition metal other than the first transition metal having a divalent oxidation state, in the presence of a surfactant in a suitable solvent, wherein the metal of the first transition metal(II) salt is selected from manganese, iron, cobalt, and nickel, and the metal of the second salt is other than the metal of the first salt; b) Adding the mixture from step a) to a suspension of open-end hollow carbon nanostructures in a suitable solvent, c) Heating the suspension to a temperature of 80-110°C to obtain a precursor material of formula (C), When step a) is carried out in the absence of another salt of the transition metal, a material of formula (C) is obtained, where t is 0; when step a) is carried out in the presence of a second salt of the transition metal, a precursor material of formula (C) is obtained, where t is different from 0 and R is a transition metal other than M''' in a divalent oxidation state.
[0218] The process for preparing the precursor material according to Clause 33, wherein step c) is performed by heating the suspension to a temperature of 80-110°C, and then step d) is performed by adding water to the suspension from step c) and heating to a temperature of 80-110°C to obtain the precursor material of formula (C).
[0219] Clause 34. Use of materials as electrocatalysts as defined in any of Clauses 1 to 17.
[0220] Clause 35. Use as described in Clause 34, as a cathode for a fuel cell, or alternatively as an anode for a water splitter.
Claims
1. A material comprising a plurality of nanorods enclosed within an open-end hollow tubular carbon nanostructure, wherein the plurality of nanorods are a) Transition metal oxides of formula (A) A z M' 2y Mn 1-x O 2 (A) or, b) Transition metal oxides of formula (B) M” 3m/n M 2-m O 3 (B) Composed of one of the following: During the ceremony, In formula (A), A is a monovalent metal, M' is a transition metal other than Mn in a divalent oxidation state, x is equal to (z / 4 + y), 0 ≤ y < 1 and 0 ≤ z < 4, and manganese can be in either the oxidation state of (IV) or a mixture of (IV) and (III), the latter representing an oxygen vacancy. In formula (B), M is a transition metal in a trivalent oxidation state selected from iron, cobalt, and nickel, M'' is a transition metal that is equal to or different from M in oxidation state n, n is a value between 2 and 6, and 0 ≤ m < 2. The transition metal oxide of formula (A) or formula (B) is present in an amount of 20-60% by weight relative to the total weight of the material. The volume of the nanorods enclosed within the hollow tubular carbon nanostructure is 50% or less of the total cavity volume of the hollow tubular carbon nanostructure. A material wherein the average inner diameter of the hollow tubular carbon nanostructure is at least twice the average thickness of the nanorod.
2. The material according to claim 1, wherein in the transition metal oxide of formula (A), y and z are 0, and in the transition metal oxide of formula (B), m is 0.
3. The material according to claim 1, wherein in the transition metal oxide of formula (A), at least one of y and z is different from 0, and in the transition metal oxide of formula (B), m is different from 0.
4. The material according to any one of claims 1 to 3, wherein the nanorod has an average thickness of 5 to 20 nm and an average length of 16 to 180 nm.
5. The nanorod is 280 nm 2 A material according to any one of claims 1 to 4, having the above surface area.
6. The material according to any one of claims 1 to 5, wherein the amount of the hollow tubular carbon nanostructure in the material is 40 to 80% by weight of the total weight of the material.
7. The material according to any one of claims 1 to 6, wherein the hollow tubular carbon nanostructure is selected from carbon nanotubes, graphitized carbon nanotubes, heteroatom-doped carbon nanotubes, carbon nanofibers, graphitized carbon nanofibers, and heteroatom-doped carbon nanofibers.
8. The material according to any one of claims 1 to 7, wherein the hollow tubular carbon nanostructure is a carbon nanotube.
9. The material according to claim 8, wherein the hollow tubular carbon nanostructure has an average inner diameter of 20 to 180 nm, an average outer diameter of 40 to 200 nm, and an average length of 10 μm or less.
10. The material according to any one of claims 1 to 9, wherein the volume of the nanorods enclosed within the hollow tubular carbon nanostructure is 10% or less of the total cavity volume of the hollow tubular carbon nanostructure.
11. An electrochemical process for preparing a material according to any one of claims 1 to 10, i) Providing a modifying electrode by coating a conductive surface with a precursor material containing a plurality of spherical nanoparticles composed of transition metal (II,III) oxides of formula (C), R t M”’ 3-t O 4 (C) The spherical nanoparticles are encapsulated within a hollow, open-end tubular carbon nanostructure. M''' is a transition metal selected from the group consisting of manganese, iron, cobalt, and nickel in divalent and trivalent oxidation states. R is a transition metal other than M''' in a divalent oxidation state. t is a value between 0 and 1, The transition metal oxide of formula (C) is present in an amount of 20-60% by weight relative to the total weight of the material. The volume of the spherical nanoparticles enclosed within the hollow tubular carbon nanostructure is 50% or less of the total cavity volume of the hollow tubular carbon nanostructure. The average inner diameter of the hollow tubular carbon nanostructure is at least twice the average thickness of the nanorod, and ii) Using the counter electrode, the reference electrode, and the modifying electrode obtained in step i), electrosynthesis of an aqueous solution containing an electrolyte selected from the group consisting of alkali or alkaline earth metal halide salts or alkali or alkaline earth metal hydroxides is performed. ii) Apply a constant current cycle of 5000 times or less in the range of -0.2 to 0.8 V with a current density of 0.5 A or more per g of precursor material, or ii) The procedure includes the step of applying a dynamic potential cycle of 5000 or less times in the range of 1 to 1.7 V at a scanning speed of 40 mV / s or more, A process in which, in the precursor material of formula (C), when M''' is manganese, a material is obtained that includes a plurality of nanorods encapsulated within the open-end hollow carbon nanostructure, wherein the plurality of nanorods are composed of a transition metal oxide of formula (A); and in the precursor material of formula (C), when M''' is a transition metal selected from the group consisting of iron, cobalt, and nickel, a material is obtained that includes a plurality of nanorods encapsulated within the open-end hollow carbon nanostructure, wherein the plurality of nanorods are composed of a transition metal oxide of formula (B).
12. A precursor material comprising a plurality of spherical nanoparticles composed of transition metal (II,III) oxides of formula (C), R t M”’ 3-t O 4 (C) The spherical nanoparticles are encapsulated within a hollow, open-end tubular carbon nanostructure. M''' is a transition metal selected from the group consisting of manganese, iron, cobalt, and nickel in divalent and trivalent oxidation states. R is a transition metal other than M''' in a divalent oxidation state. t is a value between 0 and 1, The transition metal oxide of formula (C) is present in an amount of 20 to 60% by weight relative to the total weight of the material. The volume of the spherical nanoparticles enclosed within the hollow tubular carbon nanostructure is 50% or less of the total cavity volume of the hollow tubular carbon nanostructure. A precursor material in which the average inner diameter of the hollow tubular carbon nanostructure is at least twice the average diameter of the spherical nanoparticles.
13. A process for preparing a precursor material according to claim 12, a) Providing a mixture of a transition metal (II) salt and optionally a second salt of a transition metal other than the first transition metal having a divalent oxidation state, in the presence of a surfactant in a suitable solvent, wherein the metal of the first transition metal (II) salt is selected from manganese, iron, and cobalt, and the metal of the second salt is other than the metal of the first salt; b) Adding the mixture from step a) to a suspension of open-end hollow tubular carbon nanostructures in the appropriate solvent, c) The step of heating the suspension to a temperature of 80 to 110°C, d) Add water to the suspension from step c) and heat to a temperature of 80 to 110°C to obtain a precursor material of formula (C), The process is such that when step a) is carried out in the absence of another salt of the transition metal, a material of formula (C) is obtained, where t is 0, and when step a) is carried out in the presence of a second salt of the transition metal, a precursor material of formula (C) is obtained, where t is different from 0 and R is a transition metal other than M''' in a divalent oxidation state.
14. Use of the material described in any one of claims 1 to 10 as an electrocatalyst.
15. The use according to claim 14, as a cathode for a fuel cell, or alternatively as an anode for water splitting.